Influence of Household Factors on the Utilization of Improved Gari Processing Technology in Southeastern Nigeria - K C Ekwe; I Nwachukwu (Journal of Agricultural Extension, 2006)
The influence of household faocftors on the use of improved gari processing technology developed by National Root Crops Research Institute (NRCRI) Umudike in collaboration with International Institute of Tropical Agriculture (IITA) Ibadan was appraised amongfarmers in southeastern Nigeria. Three hundred and twenty farmers were selected and inten’iewed wit the aid of structured questionnaire. The findings showed that only 42.50% of the farmers utilized all practices that constituted the technology. Results of probit model analysis revealed that marital status, educational status, household size, number of household members assisting in gari processing, participation of all household members in decision making andfarmers’ years of experience in gariprocessing were the significant householdfactors influencing the use of the technology. There thus the need to promote and popularize thisose practices in the technology, which are not yet common amongfarmers. Again extension agents need to choose contact farmfamilies which are headed by married, educated andmiddle-agedfarmersfor quicker technology adoption anddissemination.